Analisis Penerapan Akuntansi Zakat Pada Lembaga Amil Zakat Berdasarkan PSAK No 109 - Safitri, Anni; Sari, Fangela Myas; Dewi, Siska; Sholikah, Mar’atus; Kusuma, Triana Hasty (Jurnal Iqtisaduna, 2024)
This research aims to analyze the implementation of zakat accounting in zakat amil institutions based on PSAK No. 109. The type of research used is descriptive qualitative research. Data collection techniques were obtained through observation, interviews, and documentation at the Amil Zakat Al Ihsan Institute of Central Java (Laziz Jateng) Pekalongan. The data obtained is secondary data in financial position reports, changes in managed assets, cash flow reports (receivables), and primary data obtained through measurement, recognition, distribution, and presentation interviews. Based on the research analysis results, it can be concluded that the process of measuring, recognizing, distributing, and presenting the Amil Zakat Al Ihsan Institution is in accordance with PSAK No. 109. However, the financial report of the Al Ihsan Amil Zakat Institution needs to be fully up to what is implemented by PSAK No. 109.